(untitled) (Eurasian Journal of Philology Science and Education, 2026)
The article highlights A. Baitursynuly’s outstanding contribution to the formation of national terminology based on his literary heritage, with special emphasis on his work in creating drama-related terms within the Kazakh cultural and intellectual context. The study examines the ideas of the reformist scholar, one of the founders of Kazakh linguistics and Kazakh literary theory – regarding the development of national terms for drama, one of the three major literary modes (poetry, prose, drama) in Kazakh verbal art. As the first scholar to address the nature of the dramatic genre in Kazakh verbal art, Baitursynuly initiated the creation of terminology for drama, a genre which, due to its origin and historical development, has absorbed a considerable number of concepts of Greek provenance. He sought to bring such terms closer to the national worldview and to articulate them through Kazakh conceptual categories for the first time. In doing so, he laid important foundations for the theoretical meta-framework of drama, traditionally regarded as a complex and highly conventional genre. It is evident that today we have not yet fully presented and appreciated the extent of this contribution to Kazakh scholarship. Even a single work “Әдебиет танытқыш” contains multilayered knowledge that continues to invite further exploration. In particular, it would be difficult to claim that his arguments concerning dramaturgy and the terms he coined have been sufficiently examined and widely promoted. Therefore, the article provides a systematic analysis of Baitursynuly’s key concepts and terminological innovations related to dramaturgy as one of the oldest and most complex forms of literary art, and it assesses the enduring, viable principles articulated in his literary legacy. Keywords: national scholarship, verbal art, genre, dramaturgical terms, language of the literary work.